New records of cotylean flatworms (Platyhelminthes: Polycladida: Rhabditophora) from coastal habitats of Israel - Velasquez, Ximena; Bolaños, D. Marcela; Benayahu, Yehuda (Zootaxa, 2018)
Seven new records of cotylean flatworms belonging to two families and four genera were identified from Israel collected in the eastern Mediterranean Sea and the northern Red Sea. The family Pseudocerotidae was represented by three genera and six species (Pseudoceros duplicinctus, Pseudobiceros apricus, Pseudobiceros damawan, Pseudobiceros murinus, Pseudobiceros stellae, and Thysanozoon brocchii), followed by the Euryleptidae with a single species (Maritigrella fuscopunctata). Pseudoceros duplicinctus is recognized as a senior synonym of Pseudoceros prudhoei and color and pattern variations are reported for Maritigrella fuscopunctata. In addition, the presence of Pericelis byerleyana in the northern Gulf of Aqaba is confirmed, illustrated, and properly described with morphological and molecular data. Pseudoceros duplicinctus and Pseudobiceros stellae represent new geographic records for the Mediterranean Sea and Pseudobiceros apricus and Pseudobiceros damawan are new for the Red Sea. Detailed morphological analysis with emphasis on the color and pattern was applied for species identifications including high quality photographs of live and fixed animals. Partial sequences of the 28S ribosomal DNA (rDNA) of four of the species were obtained and deposited in GenBank with accession numbers provided with the corresponding species description. Our results represent a significant taxonomic contribution for the diversity and distribution of the Polycladida in Israel pointing out the importance for more integrative and comprehensive surveys in these two regions to advance the knowledge of marine biodiversity worldwide and along both Israeli coasts.